Fiscal Decentralization in Specific Areas of Government A Technical Note - Leonardo Letelier S; José Luis Sáez Lozano (Centro de Investigación y Docencia Económicas, A.C., 2013)
This study makes a contribution in two basic areas. First, it sets up a model which combines efficiency as well as political economy aspects in explaining the degree of fiscal decentralization. It innovates in making explicit the benefits from better informed politicians and policy makers (Von Hayek effect) and the potential cost push effect on public services and public goods (Scale Effect) resulting from decentralization. It takes advantage of previous literature in recognizing the extent of the ideological distance between the local and the national median voter as a third factor worth considering in the social cost benefit analysis of decentralization. Second, the aforementioned effects are put into the context of specific functional areas of government, each of them having a particular set of characteristics which lead to a different degree of decentralization. The net outcome will be the result of combining the rent seeking orientation of the central government with the particular median voter demand for each different public good.